Comparison of eight weeks rhythmic gymnastics, pilates and combined training in terms of some physical, physiological and motoric parameters - Polat, S. C.; Günay, M. (International Journal of Human Movement and Sports Sciences, 2016)
A long and hard preparation process to improve motoric characteristics and technical requirements is needed for rhythmic gymnasts to become a competitor. Studies show that positive effects of pilates on body, resemble the effects of rhythmic gymnastics. This study is based on the idea that the preparation period for long rhythmic gymnastics training could be shortened by the support of pilates exercises. Additionally, comparing some physical, motor and physiological parameters of rhythmic gymnasts who had just started training either for rhythmic gymnastics, pilates [mat series] or combined [rhythmic gymnastics + pilates] for 8 weeks. 30 girl gymnasts whose average ages are 7,30 ± 1,41 years participated to the study. As the measurements and interpretations are based on little girls at the age of 7, all the families' approvals have been received before the study. Flamingo balance test, plate tapping, standing broad jump, sit-up test for 30 seconds, sit and reach flexibility test, bent arm hang, 10x5 m running and shuttle running test were performed pre and post training. Visual and auditory reaction and hand grip strength measurements were also included. Data analysis is conducted in SPSS 22.0 software package. Pre and posttest parameters were compared with Anova and Kruskall Wallis tests for significance and distribution of the data was tested with Shapiro-Wilk test. Significant development was observed for visual and auditory reaction, tapping plate, standing broad jump, 30 second sit-up test, sit and reach flexibility test, bent arm hang, 10×5m running in pilates training group; auditory reaction, 30sec sit-up, sit and reach flexibility in rhythmic gymnastics and pilates + rhythmic training groups. The results showed that rhythmic gymnastics training accompanied by pilates are more beneficial for the fundamental level girl gymnasts.